A clip domain serine protease involved in moulting in the silkworm, Bombyx mori: cloning, characterization, expression patterns and functional analysis. Issue 5 (9th June 2017) - Liu, H.‐W.; Wang, L.‐L.; Meng, Z.; Tang, X.; Li, Y.‐S.; Xia, Q.‐Y.; Zhao, P.
Abstract: Clip domain serine proteases (CLIPs), characterized by one or more conserved clip domains, are essential components of extracellular signalling cascades in various biological processes, especially in innate immunity and the embryonic development of insects. Additionally, CLIPs may have additional non‐immune functions in insect development. In the present study, the clip domain serine protease gene Bombyx mori serine protease 95 ( BmSP95 ), which encodes a 527‐residue protein, was cloned from the integument of B. mori . Bioinformatics analysis indicated that BmSP95 is a typical CLIP of the subfamily D and possesses a clip domain at the N terminus, a trypsin‐like serine protease (tryp_spc) domain at the C terminus and a conserved proline‐rich motif between these two domains. At the transcriptional level, BmSP95 is expressed in the integument during moulting and metamorphosis, and the expression pattern is consistent with the fluctuating 20‐hydroxyecdysone (20E) titre in B. mori . At the translational level, BmSP95 protein is synthesized in the epidermal cells, secreted as a zymogen and activated in the moulting fluid. Immunofluorescence revealed that BmSP95 is distributed into the old endocuticle in the moulting stage. The expression of BmSP95 was upregulated by 20E. Moreover, expression of BmSP95 was downregulated by pathogen infection. RNA interference‐mediated silencing of BmSP95 led to delayed moulting from pupa to moth. These results suggest that BmSP95 is involved in integument remodelling during moulting and metamorphosis.